(untitled) (Quest Journal of Management and Social Sciences, 2021)
Background: Becoming environmentally viable, lately, ‘Going Green’ has been a popular expression for both worldwide banking and financial areas just as for the overall population. Green banking as a piece of going green is another method of playing out the financial organizations thinking about the clean natural issues and corporate social duty of banks. Objectives: This paper tries to investigate banker’s overall arrangement and elements influencing their viewpoint on green banking performances. Method: The information was gathered between June–October 2019 from various banks in Kathmandu valley, Nepal. The sample of 326 financial representatives has been gathered by utilizing a purposive sampling technique. Collecting primary and secondary data, this study utilizes an explanatory research design that assesses the causal relationship among reliant and free factors. The paper utilizes descriptive and inferential techniques for assessment. For understanding green financial mindfulness of the bankers, an index has been calculated. Result: The outcomes show that large numbers of the bankers are less mindful of green financial practices in their banks, while just 5% of respondents know about green banking practices. The Probit regression results uncover that education, preparing for green banking, fixed expense, client fascination, related parties’ directions, and security of the climate have critical and constructive impacts on green financial practices in banks. Conclusion: All in all, for the selection of green financial practices, most importantly, banks ought to provide training to their employees and offer effective online services to their clients.